PANDANGAN RIBA DAN BUNGA; PERSPEKTIF LINTAS AGAMA DAN PERBEDAANNYA DENGAN SISTEM BAGI HASIL DALAM EKONOMI ISLAM - Didi Suardi (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2019)
[English] This study aims to find out about “Riba” based on a cross-religious view applied to the conventional bank interest system and profit sharing system in Islamic economics, knowing what theoretical framework is used in both systems and differences in the application between conventional bank interest systems and profit sharing systems according to Islamic economic principles. The method used in this study is an analytical descriptive method that discusses perspective across religions about “Riba” and comparative analytical methods to find out the differences conventional bank interest system with profit sharing in Islamic economics. The conclusion of this study the existence of conventional bank system interest has been criticized by various circle and religions, while the validity of profit sharing has nothing to criticize. The difference both of them is related to the agreement when the contract was made on a conventional bank system and an Islamic economic profit-sharing system. The percentage of interest in conventional bank system is based on the amount of money borrowed, while the percentage of profit in Islamic economics is based on the amount of profit to be obtained. [Indonesia] Penelitian ini bertujuan untuk mengetahui tentang